Measuring the top Yukawa coupling at 100 TeV. (20th January 2016) - Mangano, Michelangelo L; Plehn, Tilman; Reimitz, Peter; Schell, Torben; Shao, Hua-Sheng
Abstract: We propose a measurement of the top Yukawa coupling at a 100 TeV hadron collider, based on boosted Higgs and top decays. We find that the top Yukawa coupling can be measured to 1%, with excellent handles for reducing systematic and theoretical uncertainties, both from side bands and from ratios.